Análisis semántico y hermenéutico del término pachayachachiq o pachayachiq - Cisneros Ayala, Claudia (2024)
With the writing, the intention is to find the original and cultural meaning of ˂pachayachiq˃ by correcting its own writing and bringing it to the form of cultural understanding of its speakers. The name has the addition of the particle [-cha-] in its internal structure as ˂pachaya[cha]chiq˃ in Campodónico y Pease (1982, p. 56). The analysis was supported by bibliographic sources. The writing was carried out with philological - hermeneutic methods. Thus, <pacha> designates ˂ allpa pacha [...] “el planeta tierra”˃ ( Jacobs, 2020, def./ earth). Also, “space, time, universe, world, earth, farmland, etc.”. The word can generate its base extension by combining with the particles ˂- chi-˃ “idea de hac-” and the causative -agentive ˂- q-˃ ˂el que o la que˃, finally, ˂pachayachiq˃ is “the one who makes land, space and time of something non existent as a natural process”.